PENGEMBANGAN PANDUAN BIMBINGAN KARIER UNTUK MENINGKATKAN KEMATANGAN KARIER SISWA SMA TINGKAT XI - Aldi Al Mu'min; Euis Eti Rohaeti; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
The problems to be revealed: 1) How is the process of developing career guidance guides to improve the career maturity of XI level high school students, 2) How is the feasibility of developing career guidance guides to increase career maturity of XI level high school students, 3) How are students' responses in developing career guidance guides to increase the career maturity of high school students level XI, 4) How effective is the development of career guidance guides to improve the career maturity of high school students level XI. The method used is Research and development (R & D). This study uses analysis of student needs in the form of a career maturity questionnaire, data collection by distributing questionnaires. The instruments used in this study were 1) an assessment sheet on the career guidance guide from media, material and practitioner experts, 2) a career maturity questionnaire, 3) a student response questionnaire to the career guidance guide.